2022
DOI: 10.3390/md20120773
|View full text |Cite
|
Sign up to set email alerts
|

Conus regius-Derived Conotoxins: Novel Therapeutic Opportunities from a Marine Organism

Abstract: Conus regius is a marine venomous mollusk of the Conus genus that captures its prey by injecting a rich cocktail of bioactive disulfide bond rich peptides called conotoxins. These peptides selectively target a broad range of ion channels, membrane receptors, transporters, and enzymes, making them valuable pharmacological tools and potential drug leads. C. regius-derived conotoxins are particularly attractive due to their marked potency and selectivity against specific nicotinic acetylcholine receptor subtypes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…The very interesting molecules with antinociceptive activity are conotoxins (Table 3). These peptides from cone snails are potent and highly selective blockers or modulators of ion channel functions [46]. O represents hydroxyproline residue.…”
Section: Peptides Derived From Sea Snailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The very interesting molecules with antinociceptive activity are conotoxins (Table 3). These peptides from cone snails are potent and highly selective blockers or modulators of ion channel functions [46]. O represents hydroxyproline residue.…”
Section: Peptides Derived From Sea Snailsmentioning
confidence: 99%
“…For example, α-conotoxin RgIA, the peptide containing 13 amino acid residues with two intramolecular disulfide bonds (Table 3), was isolated from Conus regius [46]. It has been reported that in rat models of neuropathy, RgIA is a potent pain-relieving compound.…”
Section: Peptides Derived From Sea Snailsmentioning
confidence: 99%
“…The first indications of the analgesic effects mediated by α9α10 nAChR arose when this receptor subtype was identified as a molecular target for analgesic α-conotoxins Vc1.1 and RgIA, which alleviated neuropathic pain in rodent models (reviewed in [ 196 , 197 , 198 ]). In particular, α-conotoxin RgIA (daily i.m.…”
Section: α7- and α9-containing Nachrs In Chronic Painmentioning
confidence: 99%
“…Although α-conotoxins specific to α9α10 nAChR hold great pharmacological potential, they are not ideal therapeutic drug leads due to a number of shortcomings, such as a short half-life in vivo, unstable disulfide bonds, limited modes of administration and poor potency at human nAChRs for some of them [ 230 , 231 , 232 ]. In recent reviews [ 197 , 198 ], the established strategies for improving the activity, selectivity and stability of α-conotoxins have been considered in detail. They include scanning mutagenesis, unnatural amino acid substitutions, disulfide bond modification, backbone and side-chain cyclization and polymerization.…”
Section: α7- and α9-containing Nachrs In Chronic Painmentioning
confidence: 99%
“…Each species of cone snail can secrete 50–200 different kinds of small molecule polypeptides, called conotoxins, in their venom duct, which possess rich pharmacological activities [ 19 , 20 ]. With the improved accuracy of detection technology, it is conservatively estimated that there are over hundreds of thousands of distinct neuroactive conopeptides [ 21 , 22 ]. Among the abundant conotoxins, α-conotoxins from the A-superfamily are the largest subfamily.…”
Section: Introductionmentioning
confidence: 99%